2001
DOI: 10.1002/bem.93
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic damage in human lymphocytes following GMSK phase modulated microwave exposure

Abstract: The present study investigated, using in vitro experiments on human lymphocytes, whether exposure to a microwave frequency used for mobile communication, either unmodulated or in presence of phase only modulation, can cause modification of cell proliferation kinetics and/or genotoxic effects, by evaluating the cytokinesis block proliferation index and the micronucleus frequency. In the GSM 1800 mobile communication systems the field is both phase (Gaussian minimum shift keying, GMSK) and amplitude (time domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(32 citation statements)
references
References 31 publications
4
27
0
1
Order By: Relevance
“…In addition to the above, d 'Ambrosio et al [2002] recently reported that RF exposure of diluted blood exposed in vitro to a 1.748 GHz GMSK modulated signal for 15 min at a reported maximum SAR of approximately 5 W/kg, resulted in the induction of micronuclei. The exposure system consisted of two coax-to-wave guide adapters connected end to end; a flask with cells was somehow supported within the resulting cavity.…”
mentioning
confidence: 84%
“…In addition to the above, d 'Ambrosio et al [2002] recently reported that RF exposure of diluted blood exposed in vitro to a 1.748 GHz GMSK modulated signal for 15 min at a reported maximum SAR of approximately 5 W/kg, resulted in the induction of micronuclei. The exposure system consisted of two coax-to-wave guide adapters connected end to end; a flask with cells was somehow supported within the resulting cavity.…”
mentioning
confidence: 84%
“…Several in vitro studies of micronucleus induction in mouse embryo fibroblasts [Bisht et al, 2002], human leucocytes [Tice et al, 2002;McNamee et al, 2003;Zeni et al, 2003] and human lymphocytes [d 'Ambrosio et al, 2002;Vijayalaxmi, 2006] have been published since 1998. Only one reported statistically significant effects; increased micronucleus frequency was found following exposure to a 1748 MHz phase-modulated RF field, but not after corresponding exposure to a CW field [d' Ambrosio et al, 2002].…”
Section: Review Of Experimental Observations Genotoxicitymentioning
confidence: 99%
“…Only one reported statistically significant effects; increased micronucleus frequency was found following exposure to a 1748 MHz phase-modulated RF field, but not after corresponding exposure to a CW field [d' Ambrosio et al, 2002]. Juutilainen et al [2007] investigated the effects of long-term exposure to three different mobile phone signals in three strains of mice.…”
Section: Review Of Experimental Observations Genotoxicitymentioning
confidence: 99%
“…d 'Ambrosio et al [2002] investigated whether cell cycle progression or MN induction could be caused in human lymphocyte cultures from exposure to 1.748 GHz phase modulated with Gaussian minimum shift keying (GMSK). This study was performed without the concurrent TDMA amplitude modulation used in GSM 1800 mobile phone systems.…”
Section: Mammalian Live Tissues and Cells Exposed In Vitromentioning
confidence: 99%